Traditional Knowledge, Use, and Management of Moringa oleifera Among the Mijikenda Community in Kilifi, Kenya - Boniface Mwami; Anna Maňourová; Prasad S. Hendre; Alice Muchugi; Vladimir Verner; Patrick Kariuki; Naji Sulaiman; Zbynek Polesny (Plants)
Although Moringa oleifera Lam. (Moringaceae) is a multipurpose tree with remarkable nutritional and therapeutic benefits, it is undervalued and neglected in Kenya, as the local people associate it with famine and poverty. The present study aims to assess and document the traditional knowledge on use and management as well as production constraints of the species among the Mijikenda community in Kilifi County, Kenya. We found that the plant is locally used as food and medicine for various ailments, including diabetes, high blood pressure, ulcers, stomach aches, and body pains. In addition, the plant is used for fencing and as a source of fuel. Watering and pruning were found to be the main management practices of the plant. Slightly more than half (51.3%) of the respondents reported pests as a constraint in growing the plant, while the bitter taste (60.5%) and small leaves (36.8%) were deterrents to its consumption and harvesting, respectively. More than half (55.3%) of the respondents had between one and five trees in their compounds, indicating a low preference for the plant compared to major crops. The plant species is undervalued compared to locally grown major crops, highlighting the need for concerted efforts to raise awareness of its potential benefits and address the production challenges.